Advances in Stored Product Protection. Proceedings of the 8th International Working Conference on Stored Product Protection, Yo 2003
DOI: 10.1079/9780851996912.0486
|View full text |Cite
|
Sign up to set email alerts
|

Multitarget environmental approach for control of growth and toxin production by Fusarium culmorum using essential oils and antioxidants.

Abstract: Twenty-three essential oils and six antioxidants were screened for control of growth of the mycotoxigenic species Fusarium culmorum. Of these, three essential oils (bay, clove and cinnamon oil) and two antioxidants (propyl paraben and hydroxymethylanisole) were found to be effective in controlling growth in the at concentrations of 50-200 ppm at 15°C and 25°C over the range 0.995 to 0.955 water activity (aw). More detailed studies were carried out to examine the efficacy of interactions between water activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 0 publications
2
15
0
1
Order By: Relevance
“…The effects of essential oil of clove and its principal components eugenol, on growth and mycotoxin production by some toxigenic fungal genera like Aspergillus spp., Penicillium spp., and Fusarium spp. had been reported previously (Cairns and Magan 2003, Hope et al 2003, Velluti et al 2003, 2004. This component was able to inhibit both growth and/or mycotoxin production (Bluma and Etcheverry 2008).…”
Section: Discussionmentioning
confidence: 64%
“…The effects of essential oil of clove and its principal components eugenol, on growth and mycotoxin production by some toxigenic fungal genera like Aspergillus spp., Penicillium spp., and Fusarium spp. had been reported previously (Cairns and Magan 2003, Hope et al 2003, Velluti et al 2003, 2004. This component was able to inhibit both growth and/or mycotoxin production (Bluma and Etcheverry 2008).…”
Section: Discussionmentioning
confidence: 64%
“…Growth rate stimulation was observed in some cases when Aspergillus section Flavi grew with the lowest concentration of peperina and peppermint essential oils; however, this stimulation did not occur in all aflatoxigenic isolates. The stimulation on growth rate and mycotoxin production by suboptimal concentration of different essential oils was observed by Cairns and Magan (2002) and Hope et al (2002). Under these conditions, active growth is likely to occur and the imposition of stress could result in a survival or defence response by enhanced mycotoxin production .…”
Section: Discussionmentioning
confidence: 94%
“…2000). Some studies have shown that specific essential oils and phenolic compounds can control the growth rate and spore germination time of spoilage fungi (Hope et al . 2003).…”
Section: Resultsmentioning
confidence: 99%